PENGARUH EDUKASI MENSTRUASI TERHADAP PEMAHAMAN DAN KESIAPAN MENGHADAPI MENSTRUASI BAGI SISWI KELAS V MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Zahrotul Nadhifah, Dita; Iswandi, Irvan; Utami, Dewi (Sindoro: Cendikia Pendidikan, 2024)
Puberty or the transition from childhood to adulthood is one phase of human life. Teenagers will experience physical, mental and social changes throughout this time as part of puberty. Today, puberty hits many children much earlier than in the past. Lack of understanding is a problem faced by children aged puberty, which is actually not much different. Stress may arise when a child develops faster than other children because they feel different. This research aims to find out whether menstruation education in princess activities can influence the understanding and readiness of grade 5 female students in dealing with the menstruation they will experience and whether there are changes in attitudes, beliefs and stigma towards menstruation after female students take part in education through princess activities. The approach taken in this research uses a mixed methods research approach which emphasizes quantitative research. This research uses a sequential mixed methods strategy, especially a sequential explanatory strategy. The results of the research show that the P value obtained is 0.000 < α which is set at 0.05, meaning that there is a significant impact of menstruation education through women's education activities on increasing understanding and readiness to face menstruation in grade 5 female students at MI Ma'had Al-Zaytun. Keywords: Education, Menstruation, Princess Activities